Value of serum fibronectin for assessment of liver fibrosis in chronic hepatitis C virus patients - Ahmed A Ghafar; Elsayed Ghoneem; Ramy H Agwa; Ahmed Akef; Ahmad S.H Hasan; Nahed Abdallah (SpringerOpen, 2019)
Background The stage of liver fibrosis is the most important predictive factor for initiation and duration of antiviral treatment, where patients with early fibrosis stages respond to treatment better with a higher sustained virologic response rate. Several noninvasive tests to stage the degree of fibrosis in patients with chronic hepatitis C virus (HCV) infection have been used. No single test is known to have high accuracy and the results of each test must be carefully interpreted. The objective of the study is to evaluate the value of serum fibronectin (FN) as a noninvasive predictor for the assessment of HCV-induced liver fibrosis. Patients and methods A total of 100 patients with chronic HCV infection proved by HCV antibodies and HCV RNA preparing for antiviral treatment were exposed to full history, physical examination, and laboratory assessment. Serum FN level and fibroscan were done for all patients. According to the results of fibroscan, the patients were divided into four groups of liver fibrosis and compared. Results All patients were proved to have HCV viremia with average PCR of 1990.52±3144.29 copies/ml. A statistically significant difference was found as regards FN, fibroscan, and APRI score between patients with fibrosis in comparison to patients without fibrosis. According to fibroscan results, 20 patients were found with fibrosis stage 0, 24 patients with stage 1, 24 patients with stage 2, eight patients with stage 3, and 24 patients with stage 4 (cirrhosis). On comparison of different stages of fibrosis as regards FN level, we found no statistically significant difference between stages. FN have a sensitivity of 67.5% and a specificity of 47.4% with 84.4% positive predictive value. Conclusion FN is a good noninvasive marker for the assessment of liver fibrosis in patients with chronic HCV. Larger scale multicenter studies are needed to assess its validity in the detection of fibrosis caused by causes other than HCV.